2023
DOI: 10.3389/fnins.2023.1182720
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of human TERA2.cl.SP12 stem cell-derived neurons in ultra-long-term culture for antiseizure drug discovery

Abstract: Modeling the complex and prolonged development of the mammalian central nervous system in vitro remains a profound challenge. Most studies of human stem cell derived neurons are conducted over days to weeks and may or may not include glia. Here we have utilized a single human pluripotent stem cell line, TERA2.cl.SP12 to derive both neurons and glial cells and determined their differentiation and functional maturation over 1 year in culture together with their ability to display epileptiform activity in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Human [TERA2.cl.SP12] stem cell derived neurons and glial cells were successfully differentiated and maintained for up to 88 weeks in cell culture. As previously detailed, neurons and glia differentiated and matured over the course of 4-6 months with increased axodendritic networks and synapse formation continuing through 12 months (Salmanzadeh et al, 2023). Figure 1 shows a snapshot of neurons and glia in phase contrast (Figures 1A, D) and immunolabeled (Figures 1B, C) over the course of year 1.…”
Section: Neuroglial Culturessupporting
confidence: 52%
See 4 more Smart Citations
“…Human [TERA2.cl.SP12] stem cell derived neurons and glial cells were successfully differentiated and maintained for up to 88 weeks in cell culture. As previously detailed, neurons and glia differentiated and matured over the course of 4-6 months with increased axodendritic networks and synapse formation continuing through 12 months (Salmanzadeh et al, 2023). Figure 1 shows a snapshot of neurons and glia in phase contrast (Figures 1A, D) and immunolabeled (Figures 1B, C) over the course of year 1.…”
Section: Neuroglial Culturessupporting
confidence: 52%
“…In the present study, therefore, we have addressed the hypothesis that fenamate NSAIDs have antiseizure properties by utilizing human stem cellderived neuron-glial cells maintained in long-term culture. We have recently reported that this 2D in vitro model forms complex excitatory (glutamatergic) and inhibitory (GABAergic) neural circuits over many weeks, paralleling in vivo development, with synaptogenesis and electrophysiological activity facilitated by the secondary development of astrocytes in the cultures; significantly, we have also shown that these human neuronal cell networks generate epileptiform activity in response to diverse convulsant agents and to be highly sensitive to the anticonvulsant actions of first, second and third generation antiepileptic drugs (Salmanzadeh et al, 2023).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations